Analisis Dan Perancangan Sistem Informasi Sharing File Berbasis Web Sebagai Pendukung Proses Kerja Pada Pada CV. Conslink Teknikindo - Pratiwi, Bintang; Effendy, Marwan; Khim, Soei (Jurnal Informatika Kesatuan, 2023)
Information Systems file sharing is an important aspect of organizational workflow. CV. Conslink Teknikindo, a company engaged in environmental consulting services. This study aims to design and build a web-based file sharing information system that can help CV. Conslink Teknikindo to improve the process of sharing files and managing documents within the organization. The method used in this study is system requirements analysis, system design, and web-based application development. Analysis of system requirements involves identifying the needs and requirements needed in managing file sharing. Based on the results of the needs analysis, a system design was carried out which included database design, user interface, and system workflow. After that, web-based application development was carried out using the Agile method. It is hoped that this designed and built file sharing information system will provide significant benefits for CV. Conslink Teknikindo in improving efficiency, accuracy and control over the management of their file sharing. In addition, this system can also be a reference for other companies that have similar needs in managing petty cash funds.